2011
DOI: 10.1371/journal.pone.0027341
|View full text |Cite
|
Sign up to set email alerts
|

A Map of Copy Number Variations in Chinese Populations

Abstract: It has been shown that the human genome contains extensive copy number variations (CNVs). Investigating the medical and evolutionary impacts of CNVs requires the knowledge of locations, sizes and frequency distribution of them within and between populations. However, CNV study of Chinese minorities, which harbor the majority of genetic diversity of Chinese populations, has been underrepresented considering the same efforts in other populations. Here we constructed, to our knowledge, a first CNV map in seven Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 59 publications
(101 reference statements)
9
43
0
1
Order By: Relevance
“…The quality control was the same as our previous study. 9 Samples which did not pass quality control were removed from subsequent analysis. We also removed the loci that showed difference (F ST 40) between combined calling results (all samples) and separate calling results (three ethnic groups).…”
Section: Samples and Cnv Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality control was the same as our previous study. 9 Samples which did not pass quality control were removed from subsequent analysis. We also removed the loci that showed difference (F ST 40) between combined calling results (all samples) and separate calling results (three ethnic groups).…”
Section: Samples and Cnv Detectionmentioning
confidence: 99%
“…We used an ExpectationMaximization algorithm to calculate the allele frequency by assuming that each CNV locus was in Hardy-Weinberg equilibrium, as in our previous study. 9 For each deletion or duplication allele in the admixed populations, the expected allele frequency was calculated as the sum of allele frequency of each ancestral source population weighted by its admixture proportion. Population differentiation for each CNV locus between each pair of populations was measured using the widely used pairwise F ST 13 based on the inferred allele frequency.…”
Section: Building the Cnv Map Of Xinjiang Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…All probe coordinates in this study were mapped to human genome build GRCh37/hg19. We followed two different approaches for constructing a CNV map, which are: (1) so-called copy number variable region (CNVR) using any-overlap criterion 4,8,[11][12][13][16][17][18][20][21] and (2) copy number variable cytogenetic region (CNVcR) representing any cytogenetic region that contains one or more CNVs. The study protocol is shown in Supplementary Figure S1.…”
Section: Cnv Detectionmentioning
confidence: 99%
“…[8][9] Many such cohorts exhibited inter-and intra-population differences in CNV frequency distributions. [10][11][12][13][14][15][16][17][18][19][20][21][22] In addition to disease risk, these differences, furthermore, explain a significant proportion of normal phenotypic variation. [23][24][25][26] In this context, we characterized the genome-wide architecture of CNVs in 286 healthy, unrelated subjects characterized for musical aptitude and related traits.…”
Section: Introductionmentioning
confidence: 99%